2004
DOI: 10.21273/hortsci.39.7.1614
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Exotherm and Electrolyte Leakage Measured at High Frequency of Satsuma Mandarin Exposed to Subfreezing Temperatures

Abstract: The current study was conducted to relate ice formation to the pattern and rate of leaf and stem injury of Satsuma mandarins on trifoliate orange rootstock. Potted trees were unacclimated, moderately acclimated or fully acclimated by exposing trees to 32/21 °C, 15/7 °C or 10/4 °C, respectively. Freezing treatments consisted of decreasing air temperature at 2 °C·h-1 until ice formed as evidenced by exotherms determined using differential thermal analysis of stems. Air temperature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The freezes of 1990-91 and 2000-01 caused no visible injury and had differences in T c and minimum air temperatures of 0.3 and 0.4 °C, respectively. These freezes were of suffi ciently short duration and temperatures mild enough, compared to T c , that the injury was not lethal (Ebel et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The freezes of 1990-91 and 2000-01 caused no visible injury and had differences in T c and minimum air temperatures of 0.3 and 0.4 °C, respectively. These freezes were of suffi ciently short duration and temperatures mild enough, compared to T c , that the injury was not lethal (Ebel et al, 2004b).…”
Section: Resultsmentioning
confidence: 99%
“…The upper limit of the model should correspond to injury that typically occurs for nonhardened leaves, which occurs at higher temperatures than cold-hardened leaves (Nesbitt et al, 2002). Injury occurs within 30 min after ice begins to form, which is about -4 °C for nonhardened satsuma mandarin leaves (Ebel et al, 2004b). In both cold-hardened and nonhardened citrus trees, one or a few sites promote crystallization of water, and additional water crystallizes to the ice creating an ice/water front that spreads throughout the entire canopy at rates up to 60 cm•min -1 (Yelenosky, 1991b).…”
Section: Theoretical Development Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have typically concluded that citrus develop plant water deficits during winter (Ebel et al, 2004;Thomashow, 1999;Yelenosky, 1975Yelenosky, , 1982Yelenosky, , 1985. Most of these studies were conducted without adequate knowledge of soil moisture content or were conducted in dry soils that imposed drought stress.…”
mentioning
confidence: 99%
“…There are several lines of evidence that would suggest that at least some changes in plant water deficits occur as a result of cold temperatures and not dry soil. Stomatal aperture and leaf water potential are typically reduced even on days of very low evaporative demand and after the trees have been fully irrigated (Ebel et al, 2004;Yelenosky, 1982).…”
mentioning
confidence: 99%